Economic and social upgrading in global value chains insights from Philippine manufacturing firms - Mendoza, Adrian R. (2018)
This study explores results of the 2012 Survey on Adjustments of Establishments to Globalization (SAEG) to analyze the economic and social upgrading experience of Philippine manufacturers within global value chains (GVCs). Three broad patterns emerge from the data. First, firms with stronger GVC linkages tend to have better labor indicators than purely domestic producers. Second, the majority of manufacturers either experienced or missed economic and social upgrading simultaneously. Lastly almost all social upgrading is accompanied by economic upgrading but economic upgrading may take place without a social component. Against this background, this study uses bivariate profit regression to model the joint determination of the two separate but interconnected upgrading outcomes. The results indicate that the covariates in the model can be categorized based on their statistical significance: purely economic (i.e., employment size, unit labor cost, high skill intensity, and the Kaitz dummy),purely social (i.e., training, female intensity, and foreign equity), and both (i.e. contractualization, and process and product innovations).

This results have several important implications. First, GVC firms' notion of social upgrading is closer to the softer components of working conditions than to traditional measurable indicators such as employment, wages, and efficiency. Second, the results suggest direct and indirect channels through which technological upgrading may generate desirable social outcomes: the direct channel highlights that innovation should be accompanied by skills development to sustain higher value creation while the indirect channel underlines the potential of innovation to create upward spirals in output, productivity, and, that the social benefits of economic upgrading may not be evenly distributed among different types of employment. Overall, the results emphasize the need for a holistic upgrading experience that shifts the country's comparative advantage from cheap labor to innovate local industries and highly skilled workers.
Keywords: Globalization